2020
DOI: 10.1097/spv.0000000000000843
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Transperineal Gender-Affirming Vaginectomy and Colpocleisis

Abstract: Objectives There are multiple approaches to vaginectomy for the purpose of masculinizing gender-affirming genital surgery including mucosal fulguration and excision. The outcomes of the approaches are not well described. We aim to describe the surgical outcomes of gender-affirming vaginectomy and colpocleisis by complete mucosal excision. Methods We performed a case series study of 40 transmasculine patients who underwent gender-affirming vaginectomy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Hougen et al reported no instances of fistula to the vaginal space, mucocele from the vaginal remnant, or visceral injury (bladder injury, bowel injury, ureteral obstruction) in a series of 40 transgender males undergoing total vaginectomy and colpocleisis. 37 In the largest series to date, Nikkels et al found that 15 (10%) of 143 patients had major perioperative complications, including 1 rectal injury and 9 bladder/urethral injuries. 36 Laparoscopic and robotic approaches to vaginectomy have also been described 31,38 with similarly low rates of major complications and with less blood loss.…”
Section: Vaginectomymentioning
confidence: 99%
“…Hougen et al reported no instances of fistula to the vaginal space, mucocele from the vaginal remnant, or visceral injury (bladder injury, bowel injury, ureteral obstruction) in a series of 40 transgender males undergoing total vaginectomy and colpocleisis. 37 In the largest series to date, Nikkels et al found that 15 (10%) of 143 patients had major perioperative complications, including 1 rectal injury and 9 bladder/urethral injuries. 36 Laparoscopic and robotic approaches to vaginectomy have also been described 31,38 with similarly low rates of major complications and with less blood loss.…”
Section: Vaginectomymentioning
confidence: 99%
“…Colpectomy is associated with significant blood loss [36] . However, there are limited reports of estimated blood loss during metoidioplasty procedures.…”
Section: Bleeding Complicationsmentioning
confidence: 99%
“…Nikkels et al evaluated 143 transgender patients undergoing colpectomy with or without additional procedures such as metoidioplasty and hysterectomy [36] . A bladder injury was reported in 6 patients (4%) and bowel (rectal) injury in 1 patient (1%).…”
Section: Bladder and Lower Gastrointestinal Injurymentioning
confidence: 99%
“…Hysterectomy and salpingo-oophorectomy are commonly performed using a transvaginal or standard laparoscopic approach during a separate stage in advance of masculinizing genital surgical procedures [13] . A primary advantage of this staging is to avoid the longer operative times, increased procedural blood loss, and greater physiologic disturbance when combining these with other procedures [14] . Note that chest recontouring can be performed at the same time as hysterectomy and salpingo-oophorectomy.…”
Section: Hysterectomy Salpingo-oophorectomy Vaginectomymentioning
confidence: 99%
“…For vaginectomy, there is variation in the specific technique used to ablate the vaginal mucosa. Although direct surgical excision may entail more blood loss, and although fulgarization may result in a higher chance of retained vaginal mucosa, at present, there appear to be limited data [14] indicating the superiority of any one of the three commonly employed methods: fulgarization [15] , direct surgical excision [16] , or dual-approach, robotically assisted excision [17] . The selected method depends on surgeon expertise and preference and on the staging and specific method of pars fixa construction.…”
Section: Hysterectomy Salpingo-oophorectomy Vaginectomymentioning
confidence: 99%